Teratoma during Pregnancy with Positive Estrogen and Progesterone Receptors and Elevated Ca19-9 Antigen Levels. (16th October 2012) - Kanlioglu Kuman, Nilgun; Cokpinar, Salih; Yaman, Ertan; Meteoglu, Ibrahim; Karadag, Fisun
Abstract : We present a 27-year-old female patient admitted with an anterior mediastinal mass. She complained of chest discomfort and hemoptysis which began seven months prior. She had given birth five months prior. Thoracic X-ray showed an anterior mediastinal mass. Thorax computed tomography (CT) confirmed a well-defined anterior mediastinal mass with 13 × 12  cm diameter, extending to the right hemithorax. It was composed of cystic spaces and discrete areas like soft tissue and fat. Serum Ca 19-9 level was elevated. CT features were consistent with a mature teratoma. During median sternotomy, the tumor revealed adhesions to the right lung and the right subclavian artery. Histologically, the tumor was diagnosed as a mature teratoma. Estrogen and progesterone receptors were detected to be positive in the resected tissue. We conclude that alterations in hormone levels during pregnancy might be the cause of rapid tumor growth which leads to hemoptysis.